A consciência na primeira tópica freudiana - Cossu Junior, Franco (2000)
The principal aim of this entire work is to clarify the theorical statue about the counsciousness concept in the first freudian topography. In spite of the Uncounscious discovery and its central importance in the mental apparatus theory to the comprehension about pathologies as much as normality, the counsciousness never let to be a Freud`s constant worry, since the Studies on Histeria until the Metapsychology elaboration. If the counsciousness phenomenon, which is no longer central, may be considered an efect of surface and no more equivalent to the general psychism, it doesn`t renounce to be, although, the only way to the knowledge of the uncounscious phenomena.